ANALISIS PEMAHAMAN GURU TERHADAP KOMPETENSI PEDAGOGIK GURU: SYSTEMATIC LITERATURE REVIEW - Ninin Kurike R; Nandang Rusmana; Maulia Depriya Kembara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT This paper reports the results of research which aims to analyze teachers' understanding of teachers' pedagogical competence. This research uses the Systematic Literature Review (SLR) method. In order to save space, this article will present data obtained from nine journals that have met the in-depth inclusion criteria for publications between 2015 and 2022 to evaluate how teachers understand the pedagogical competence of teachers in elementary schools. The results of the review show that pedagogical competence includes the ability to understand the characteristics of students, design and implement educational learning, manage the class well, and utilize technology to support the learning process. However, several challenges are still found, such as the lack of use of information technology, limited facilities and infrastructure, as well as variations in learning management that are less than optimal. Supporting factors such as teacher experience and needs-based training such as In House Training are considered important to overcome this gap. Keywords: Teacher Competency, Pedagogical Competence, Primary school teachers ABSTRAK Tulisan ini melaporkan hasil penelitian yang bertujuan untuk menganalisis pemahaman guru terhadap kompetensi pedagogik guru. Penelitian ini menggunaka metode Systematic Literature Review (SLR). Demi menghemat ruang, artikel ini akan menyajikan data yang diperoleh dari sembilan jurnal yang telah memenuhi kriteria inklusi mendalam terhadap publikasi antara tahun 2015 dan 2022 untuk mengevaluasi bagaimana pemahaman guru terhadap kompetensi pedagogik guru di sekolah dasar. Hasil dari review menunjukan bahwa kompetensi pedagogik meliputi kemampuan memahami karakteristik peserta didik, merancang dan melaksanakan pembelajaran yang mendidik, mengelola kelas dengan baik, serta memanfaatkan teknologi untuk mendukung proses pembelajaran. Namun, beberapa tantangan masih ditemukan, seperti kurangnya pemanfaatan teknologi informasi, keterbatasan sarana dan prasarana, serta variasi dalam pengelolaan pembelajaran yang kurang optimal. Faktor pendukung seperti pengalaman guru dan pelatihan berbasis kebutuhan seperti In House Training dianggap penting untuk mengatasi kesenjangan ini. Kata Kunci: Kompetensi Guru, Kompetensi Pedagogik, Guru Sekolah Dasar